Effects of Nitrogen Source on Microdochium Patch of Annual Bluegrass in Western Oregon - Ruying Wang; Cole Stover; Clint M. Mattox; Brian W. McDonald; Alec R. Kowalewski (Plant Health Progress, 2026)
Microdochium patch, caused by the fungal pathogen Microdochium nivale, damages putting greens during cool and humid conditions. Previous research has determined that frequent winter sulfur applications reduce disease severity, although no research to date has focused on sulfate applied with nitrogen. A field experiment was initiated on an annual bluegrass putting green in western Oregon, a region without prolonged snow cover, to evaluate the effects of autumn and winter nitrogen rates and sources with and without sulfate-containing products applied monthly on Microdochium patch. The experiment was a 2 × 6 factorial arranged in a randomized complete block design with four replications. Nitrogen rates consisted of two levels, 4.9 and 9.8 kg N ha −1 month −1 . Nitrogen sources consisted of ammonium sulfate, ammonium thiosulfate, potassium nitrate, calcium nitrate, urea, and urea + magnesium sulfate. Nitrogen rates tested did not significantly affect Microdochium patch, whereas nitrogen source significantly influenced disease severity. Ammonium sulfate and ammonium thiosulfate treatments resulted in the lowest disease severity. Calcium nitrate and urea resulted in the highest area under the disease progress curves in both years of the study, suggesting that these nitrogen sources should be avoided for annual bluegrass fertilization when Microdochium patch is a concern. The combination of magnesium sulfate and urea reduced disease compared with urea alone only in the first trial year, suggesting that sulfate is unlikely to be solely responsible for disease suppression. This research provides practical information for golf course superintendents to develop their autumn and winter nitrogen programs in areas without snow cover.